2013
DOI: 10.1097/aln.0b013e31827d413e
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 Receptors in Mouse Pontine Reticular Formation Depress Breathing, Increase Anesthesia Recovery Time, and Decrease Acetylcholine Release

Abstract: Background Clinical and preclinical data demonstrate the analgesic actions of adenosine. Central administration of adenosine agonists, however, suppresses arousal and breathing by poorly understood mechanisms. This study tested the two-tailed hypothesis that adenosine A1 receptors in the pontine reticular formation (PRF) of C57BL/6J mice modulate breathing, behavioral arousal, and PRF acetylcholine release. Methods Three sets of experiments used 51 mice. First, breathing was measured by plethysmography after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Abbreviations: KE, ketone ester; KEKS, mix of KE and KS in a 1:1 ratio; KEMCT, mix of KE and medium chain triglyceride (MCT) oil in a 1:1 ratio; KS, ketone salt; KSMCT, mix of KS and MCT oil in a 1:1 ratio; SD, standard diet/control; *p < 0.05; ***p < 0.001; ****p < 0.0001 effects of isoflurane in dogs (e.g., EEG has been changed from a sleep pattern to an awake pattern) [30] and caffeine accelerated emergence from isoflurane-evoked anesthesia in humans [52]. Moreover, enhanced activity of A1Rs (e.g., by an A1R agonist N-sulfophenyl adenosine) may cause increase in anesthesia recovery time [53] and isoflurane may activate A1Rs [54]. It has been demonstrated that receptors of adenosine, such as inhibitory A1Rs and excitatory A2ARs are expressed brain areas implicated in the generation of sleep and sleep-like effects, such as ventrolateral/lateral preoptic area and basal forebrain [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviations: KE, ketone ester; KEKS, mix of KE and KS in a 1:1 ratio; KEMCT, mix of KE and medium chain triglyceride (MCT) oil in a 1:1 ratio; KS, ketone salt; KSMCT, mix of KS and MCT oil in a 1:1 ratio; SD, standard diet/control; *p < 0.05; ***p < 0.001; ****p < 0.0001 effects of isoflurane in dogs (e.g., EEG has been changed from a sleep pattern to an awake pattern) [30] and caffeine accelerated emergence from isoflurane-evoked anesthesia in humans [52]. Moreover, enhanced activity of A1Rs (e.g., by an A1R agonist N-sulfophenyl adenosine) may cause increase in anesthesia recovery time [53] and isoflurane may activate A1Rs [54]. It has been demonstrated that receptors of adenosine, such as inhibitory A1Rs and excitatory A2ARs are expressed brain areas implicated in the generation of sleep and sleep-like effects, such as ventrolateral/lateral preoptic area and basal forebrain [29].…”
Section: Discussionmentioning
confidence: 99%
“…3). Moreover, adenosine receptors may also modulate anesthesia recovery time [52,53]. Thus, it is possible that exogenous ketone supplements not only delay the onset of isoflurane-induced anesthesia (immobility) [23] (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, adenosine accumulates under, for example, sleep deprivation and may have a role in the anesthetic action of isoflurane [28,44]: theophylline (a non-selective antagonist of adenosine receptors) reversed the cerebral effects of isoflurane in dogs (e.g., EEG has been changed from a sleep pattern to an awake pattern) [30] and caffeine accelerated emergence from isoflurane-evoked anesthesia in humans [52]. Moreover, enhanced activity of A1Rs (e.g., by an A1R agonist N-sulfophenyl adenosine) may cause increase in anesthesia recovery time [53] and isoflurane may activate A1Rs [54]. It has been demonstrated that receptors of adenosine, such as inhibitory A1Rs and excitatory A2ARs are expressed brain areas implicated in the generation of sleep and sleep-like effects, such as ventrolateral/lateral preoptic area and basal forebrain [29].…”
Section: Discussionmentioning
confidence: 99%
“…There is an association between adenosinergic modulation of sleep, obesity-induced sleep disruption, and the impact of sleep quality and duration on the experience of pain. The present study focused on the pontine brain stem because adenosinergic transmission in the pontine reticular formation contributes to the regulation of sleep (Baghdoyan and Lydic, 2012, Gettys et al, 2013) and nociception (Kshatri et al, 1998, Tanase et al, 2002, Wang et al, 2009, Watson et al, 2010). Chronic sleep restriction facilitates development of obesity (Spiegel et al, 1999, Morselli et al, 2010), increases leptin as a modulator of pro-inflammatory cytokines (reviewed in (Hayes et al, 2011), and — even in healthy volunteers — increases pain (Roehrs et al, 2006, Haack et al, 2007).…”
Section: Discussionmentioning
confidence: 99%